Debittering of Pontianak Orange Juice using Naringinase Enzyme - Salahudin, Farid (Biopropal Industri, 2010)
The goal of this research is debittering of orange juices with enzimatic process. Naringinase enzim is produced with Penicillium decumbens. The research metode is complete random design with two variabel. The first variabel is concentration of enzim : 0,0; 200; 400 ppm and the second variabel is time of incubation : 1, 2 and 3 hours. The product of this research is tested ascorbic acid, Total Plate Count and organoleptic test. The result showed concentration of naringinase enzim 400 ppm and incubation 3 hours can eliminated the after taste of orangge juice without reduce the ascorbic acid and colour of orange juice.